Numerical study of vibration processes in composite materials with the aim of constructing delamination control system - Serovaev, Grigorii Sergeevich; Shestakov, Alexey Petrovich; Oshmarin, Dmitrii Alexandrovich (Computational Continuum Mechanics, 2017)
Composite materials, due to a number of features (high specific strength, low weight), are currently among the most common materials used to create objects for a wide range of applications. Modern safety standards require the timely control of the appearance and development of defects, in particular, delaminations. In this regard, close attention is paid to the development and improvement of damage detection methods. In this paper, a numerical study of the possibility of detecting and localizing delaminations in the structures made from layered composite materials using vibrational approaches is presented. The proposed method is based on the excitation of oscillations of increased amplitude in the defect region. This is possible because of the appearance of natural frequencies, at which the largest amplitude is localized in the defect region. In the course of the study, a weak dependence of such natural vibration frequencies on the location of the defect on the structure and a strong dependence on the size of the delamination were revealed. At the next stage, numerical simulation of forced steady-state oscillations is performed taking into account the dissipative characteristics of the composite material necessary for reliable description of the vibrational processes in the structure. The frequency of the external excitation is chosen in accordance with the natural oscillation frequency corresponding to the defect obtained from the modal analysis. The results of the calculations showed a significant increase in the amplitude of vibrations in the region of delamination as compared to a healthy structure if the correct selection of the frequency of the external excitation was chosen. An analysis of the effectiveness of the approach was made when removing the driving force from the location of the delamination. The presented investigation of vibration processes allows us to substantiate the possibility of creating a delamination detection system for composite materials and to determine its main parameters.